Callivelia, a new genus for certain Neotropical Veliinae (Heteroptera: Veliidae), including description of a new species - Polhemus, Dan A. (Zootaxa, 2021)
The new genus Callivelia is proposed to hold three Neotropical species previously held within Paravelia: type-species Callivelia conata (Hungerford), Callivelia taipiensis (Cheesman) and Callivelia bipunctata (Rodrigues, Moreira, Nieser, Chen & Melo). Paravelia virtutis (Drake & Harris) 1935 is synonymized under Callivelia taipiensis (Cheesman) 1926. In addition, a new species, C. anomala, is described from the Amazon Basin of Brazil. Additional distributional records are provided for the three previously described species treated, including the first country record for C. bipunctata in Paraguay. A key to the species of Callivelia is provided, accompanied by color habitus photographs for all three species, and additional photographs of key generic characters.